Feminization of Indonesian short-finned eel (Anguilla bicolor bicolor Mc Clelland, 1844) through injection of estradiol and methyl testosterone at the combination with hCG and anti dopamin - Abdul Zahri; Agus Oman Sudrajat; Muhammad Zairin Junior (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2016)
The objective of the experiment was to describe the influence of estradiol (E2) and methyltestosterone (MT) in combination with hCG and anti-dopamine (AD) on the percentage of female and quality of ovary development of Indonesian short-finned eel (Anguilla bicolor bicolor). Eel with 200±15 g of body weight in the yellow phase injected with a estradiol solution of 3mg mL-1 + hCG 2mg mL-1 + AD 10 mg mL-1 (hEA), MT 3 mg mL-1 + hCG 2 mg mL-1 + AD 10 mg mL-1 (hTA), estradiol 3 mg mL-1 + AD 10 mg mL-1 (EA), MT 3 mg mL-1 + AD 10 mg mL-1 (TA), AD 10 mg mL-1 (A) and 9 mg mL-1 NaCl control (F). Injection frequency was six times with a period of two weeks. After six weeks of experiment, EA and hTA combination hormone treatments were effective to increase the female percentage 72% and 66%, respectively. The best ovary development was found in the hTA treatment i.e. attain the late-vitellogenesis with GSI value of 4.80%. Abstrak Penelitian ini bertujuan untuk menjelaskan pengaruh estradiol (E2) dan metil testosteron (MT) yang dikombinasikan dengan hCG dan anti dopamin (AD) terhadap persentase jenis kelamin betina dan kualitas perkembangan ovari sidat (Anguilla bicolor bicolor). Sidat dengan bobot 200±15g pada faseyellow diinjeksi dengan larutan estradiol 3 mg mL-1 + hCG, 2 mg mL-1 + AD 10 mg mL-1 (hEA), MT 3 mg mL-1 + hCG 2 mg mL-1 + AD 10 mg mL-1 (hTA), estradiol 3 mg mL-1 + AD 10 mg mL-1 (EA), MT 3 mg mL-1 + AD 10 mg mL-1 (TA), AD 10 mg mL-1 (A), dan kontrol 9 mg mL-1 NaCl (F). Frekuensi injeksi sebanyak enam kali dengan periode dua minggu sekali. Pemberian hormon kombinasi dengan perlakuan hEA dan hTA ternyata efektif meningkatkan persentase jenis kelamin betina berturut-turut sebesar 72% dan 66% setelah enam minggu. Perkembangan gonad betina terbaik ditemukan pada perlakuan hTA yaitu mencapai fase vitellogenesis akhir dengan nilai GSI 4,80%